Population Ageing in India - Giridhar,G. (Ed.)....[et.al] (Delhi, 2014)
A major emerging demographic issue of the twenty-first century is the ageing of populations as an inevitable consequence of the demographic transition experienced by most countries. While all countries are experiencing growing proportions of the elderly, developing countries are currently ageing faster than developed countries. Population Ageing in India creates a holistic research base by looking at the demographics of the ageing population and reviewing existing studies. It delves deep into the socioeconomic layers of elderly health, work participation and contribution to income generation, national policy in practice and policy initiatives to ensure elderly wellbeing in other Asian countries. The shift of age composition to an older age structure has important implications for individuals, society as well as the country. Therefore, there is a need to promote harmony between development and demographic change by increasing the economic and social sources of support for the elderly.
Keywords: Population